Fluorescence activated cell sorting—A selective tool for plant cell isolation and analysis. Issue 9 (24th May 2021) - Antoniadi, Ioanna; Skalický, Vladimír; Sun, Guiling; Ma, Wen; Galbraith, David W.; Novák, Ondřej; Ljung, Karin
Abstract: Instrumentation for flow cytometry and sorting is designed around the assumption that samples are single‐cell suspensions. However, with few exceptions, higher plants comprise complex multicellular tissues and organs, in which the individual cells are held together by shared cell walls. Single‐cell suspensions can be obtained through digestion of the cells walls and release of the so‐called protoplasts (plants without their cell wall). Here we describe best practices for protoplast preparation, and for analysis through flow cytometry and cell sorting. Finally, the numerous downstream applications involving sorted protoplasts are discussed.